Myonectin and metabolic health: a systematic review - Petro, Jorge L.; Gallo-Villegas, Jaime; Calderón, Juan C. (Frontiers in Endocrinology, 2025)
Myonectin is a myokine with a potential role in metabolic health. This is a bibliometric and bioinformatics-complemented systematic review aimed to comprehensively analyze the structure, regulation and effects of myonectin on metabolic outcomes relevant to the pathophysiology of chronic metabolic diseases. Fifty-three studies involving cellular, animal, and human models were included. Findings indicate that myonectin is induced by aerobic exercise, nutrients, epinephrin, hypoxia and curcumin but is downregulated by obesity and muscle dysfunction. Evidence suggests that myonectin regulates lipid uptake and distribution across tissues, reduces inflammation and apoptosis and modulates mitochondrial function likely through the activation of AKT and AMP-activated protein kinase (AMPK)-mediated signaling pathways. While most results arising from human studies of good quality are in agreement with animal and cellular data, controversy remains and we discuss challenges and perspectives in the field. In conclusion, myonectin has a diverse role in regulating metabolic health, but a key contribution pertains to lipid regulation, which likely leads to a healthy expansion and distribution of adipose tissue.